Investigation of the inhibitory effect of Bacillus pumilus on Nannochloropsis salina - Ayshoa Al Gabara, Mirna Dheyaa, author; Reardon, Kenneth F., advisor; Argueso, Cris, committee member; Peebles, Christie, committee member (Colorado State University. Libraries, 2017)
Microalgae have the potential to be a source of a wide range of industrial materials. To provide the biomass for these products, algae are grown in large volumes. Previous research has shown that there are other microbial species living in algal cultivation systems at these scales, but little is known about the interactions among them. Some of the bacteria in algae cultivations have been identified. Some species can inhibit algal growth, while others are growth promoting. In this research, we focused on one algal species, Nannochloropsis salina, and a bacterial species, Bacillus pumilus. In previous research in our laboratory, B. pumilus culture filtrate had inhibitory effects towards N. salina. We are using these species as a model system to understand a mechanism of bacterial inhibition of algae. Specifically, we have investigated the nature of the inhibitory molecule that is produced by B. pumilus and when it is produced. Our results indicate that B. pumilus produces at least one inhibitory molecule that is probably a protein larger than 30 kD. Since the bacteria produce the highest level of the inhibitory molecule in the presence of marine broth medium (MB), we studied the effects II of the components of MB to determine whether one of these induced the production of the inhibitor more than others. B. pumilus was inoculated in artificial sea water medium (ASW) and several components of MB (peptone, yeast extract and glucose). The filtrate of B. pumilus grown in ASW supplemented with peptone or yeast extract had an inhibitory effect on N. salina, but the filtrate of B. pumilus grown in ASW supplemented with glucose had no inhibitory effect towards the algal species. The results showed that the molecule was produced regardless of the presence of the algal species and it was more concentrated at the late stationary phase. Also there was a certain algal phase when N. salina had more resistance to the inhibition of B. pumilus filtrate. The bacterial species showed the ability to grow on the filtrate of N. salina without any other added components. This knowledge about the mechanism by which this bacterial species inhibits an algae species is useful to determine whether other bacteria use the same strategy and to develop an approach to reduce this inhibitory impact.